2016
DOI: 10.1371/journal.pone.0164716
|View full text |Cite
|
Sign up to set email alerts
|

QRFP-Deficient Mice Are Hypophagic, Lean, Hypoactive and Exhibit Increased Anxiety-Like Behavior

Abstract: How the hypothalamus transmits hunger information to other brain regions to govern whole brain function to orchestrate feeding behavior has remained largely unknown. Our present study suggests the importance of a recently found lateral hypothalamic neuropeptide, QRFP, in this signaling. Qrfp-/- mice were hypophagic and lean, and exhibited increased anxiety-like behavior, and were hypoactive in novel circumstances as compared with wild type littermates. They also showed decreased wakefulness time in the early h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 39 publications
5
26
2
Order By: Relevance
“…The phenotype of QRFP‐deficient mice (Okamoto et al, ) has confirmed pharmacological data showing that 26RFa/QRFP displays orexigenic and anxiogenic properties (Chartrel et al, ; Do Rego et al, ; Moriya et al, ; Takayasu et al, ; Primeaux et al, ) and stimulates locomotor activity (Do Rego et al, ; Takayasu et al, ). Search for association between SNPs within the human QRFP gene with eating and mood disorders will be required to determine whether 26RFa/QRFP exerts similar activities in humans.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…The phenotype of QRFP‐deficient mice (Okamoto et al, ) has confirmed pharmacological data showing that 26RFa/QRFP displays orexigenic and anxiogenic properties (Chartrel et al, ; Do Rego et al, ; Moriya et al, ; Takayasu et al, ; Primeaux et al, ) and stimulates locomotor activity (Do Rego et al, ; Takayasu et al, ). Search for association between SNPs within the human QRFP gene with eating and mood disorders will be required to determine whether 26RFa/QRFP exerts similar activities in humans.…”
Section: Discussionmentioning
confidence: 74%
“…Notably, chronic administration of QRFP produced a transient increase in food intake, weight gain and adiposity in mice consuming a standard chow diet and increased body weight and adiposity in mice fed a moderately fat diet (Moriya et al, 2006). The recent observation that QRFP-deficient mice are hypophagic and lean (Okamoto et al, 2016) strongly supports the notion that 26RFa/QRFP is a potent orexigenic peptide.…”
Section: Biological and Pharmacological Effects Of Qfrp Peptidesmentioning
confidence: 79%
See 3 more Smart Citations